Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsomega.0c05037
|View full text |Cite
|
Sign up to set email alerts
|

Binder-Free, Thin-Film Ceramic-Coated Separators for Improved Safety of Lithium-Ion Batteries

Abstract: Separators play a crucial role in ensuring the safety of lithium-ion batteries (LIBs). Commercial polyolefin-based separators such as polyethylene (PE) still possess serious safety risks under abuse conditions because of their poor thermal stability. In this work, a novel type of binder-free, thin ceramic-coated separators with superior safety characteristics is demonstrated. A thin layer of alumina (Al 2 O 3 ) is coated on commercial PE separators using the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…When the temperature increases further, separator breakdown happens, i.e., large thermal shrinkage and breakage occur, causing an internal short circuit and speeding up thermal runaway of LIBs. [17] This is because films are uniaxially stretched along the machine Li-ion batteries nowadays are widely used as energy storage systems owing to their high power and energy densities. However, the safety of Li-ion batteries has increasingly become a grave concern, and how to effectively mitigate or avoid the thermal runaway of Li-ion batteries, particularly during fast charging/discharging, is a critical issue.…”
Section: A Critical Review On Materials and Fabrications Of Thermally...mentioning
confidence: 99%
See 1 more Smart Citation
“…When the temperature increases further, separator breakdown happens, i.e., large thermal shrinkage and breakage occur, causing an internal short circuit and speeding up thermal runaway of LIBs. [17] This is because films are uniaxially stretched along the machine Li-ion batteries nowadays are widely used as energy storage systems owing to their high power and energy densities. However, the safety of Li-ion batteries has increasingly become a grave concern, and how to effectively mitigate or avoid the thermal runaway of Li-ion batteries, particularly during fast charging/discharging, is a critical issue.…”
Section: A Critical Review On Materials and Fabrications Of Thermally...mentioning
confidence: 99%
“…When the temperature increases further, separator breakdown happens, i.e., large thermal shrinkage and breakage occur, causing an internal short circuit and speeding up thermal runaway of LIBs. [ 17 ] This is because films are uniaxially stretched along the machine direction (MD) in the dry manufacturing process for separators, which results in anisotropic material behaviors at high temperatures. [ 11,18–21 ] In general, the thermal stability of separators can affect their dimensional stability or shrinkage, melt rupture, and puncture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that coating high‐temperature‐resistant materials on polyolefin separators can improve thermal stability and electrolyte wettability of the separator. [ 7–12 ] Cho et al [ 13 ] coated the PE separator with amino‐functionalized SiO 2 particles to reduce the thermal shrinkage of the separator at 130 °C. Chen et al [ 14 ] coated PE separator with zeolitic imidazolate to improve its thermal stability and electrolyte wettability.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that coating high-temperature-resistant materials on polyolefin separators can improve thermal stability and electrolyte wettability of the separator. [7][8][9][10][11][12] Cho et al [13] coated the PE separator with amino-functionalized SiO 2 particles to reduce the thermal shrinkage of the separator at 130 C. Chen et al [14] coated PE separator with zeolitic imidazolate to improve its thermal stability and electrolyte wettability. However, due to the inability of high-temperature-resistant materials to form a self-supporting layer, the improvement of the thermal stability of the commercial separator is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of other methods have been developed in recent years to overcome the disadvantages of separators, including polymer composites (a blend of polymer and inorganic fillers) [ 13 , 14 , 15 , 16 , 17 ], inorganic fillers (e.g., SiO 2 , TiO 2 , Al 2 O 3 and zeolite) [ 18 , 19 , 20 , 21 , 22 , 23 ], and polymer blends [ 17 , 24 ]. Remarkably, it has been confirmed that modification of a polyolefin membrane with a blend of polymer and inorganic fillers as a coating may be the most promising approach [ 1 , 25 ].…”
Section: Introductionmentioning
confidence: 99%